A novel Ceratomyxa species (Myxozoa: Cnidaria) infecting an Amazonian catfish. (August 2022) - Araújo, Bruno L.; Adriano, Edson A.; Franzolin, Gustavo N.; Zatti, Suellen A.; Naldoni, Juliana
Abstract: Parasites are important organisms for the health of ecosystems. While the Amazon Basin is home to a great diversity of ichthyofauna, our knowledge of myxozoan diversity in the biome remains relatively limited. The present study describes a new myxozoan species, Ceratomyxa mandii n. sp., parasitizing the gallbladder of the Amazonian catfish Pimelodina flavipinnis (Pimelodidae) from the Solimões River, in the region of Manaus, Brazil. Light and electron microscopy,  small subunit ribosomal DNA (SSU rDNA) sequencing and phylogenetic analysis were performed. The new species exhibited worm-like plasmodia with undulatory motility. The SSU rDNA based phylogenetic analysis revealed it to be a sister taxon of C. gracillima, which also parasitizes an Amazonian pimelodid fish, possibly reflecting a host-parasite co-speciation process. This study contributes to our understanding of this little sampled group of organisms. Graphical abstract: Unlabelled Image Highlights: A novel Ceratomyxa species with plasmodium worm-like motility is described. The new species was found parasitizing the gallbladder of an amazonian catfish. Light and electron microscopy and sequence of the SSU rDNA were performed. The phylogeny revealed the new Ceratomyxa as sister species of C. gracillima .